Occupational segregation and gender differentials in earnings in Macedonia - Biswajit Banerjee (IZA Journal of European Labor Studies, 2014)
This paper examines gender differentials in earnings in Macedonia, with special emphasis on the role of occupational segregation. The lower earnings of women in Macedonia cannot be explained by gender differences in measured human capital endowments. There is a high degree of segregation of jobs along gender lines, the end product of which is lower earnings for women relative to men. Women are over-represented in female-dominated occupations, and feminization of occupations has a negative impact on earnings. Even after controlling for numerous individual and job characteristics and gender composition of occupations, a huge amount of the gender wage gap remains unexplained.
Keywords: J31; P2; 330; Occupational segregation; Occupational feminization; Gender wage gap; Decomposition of earnings differentials